Dynamics of seagrasses in a heterogeneous tropical reef ecosystem - Kneer, Dominik (2014)
In tropical Southeast Asia seagrasses can be found in three types of habitats: "River estuaries" (including mud flats), "Shallow Coastal / Back Reef" (including reef flats and lagoons) and "Deep Water / Deep Coastal / Fore Reef". Especially those seagrass meadows growing on reef flats are characterized by high temporal and spatial dynamics. Research conducted in the Spermonde Archipelago, Southwest Sulawesi, Indonesia, revealed that water motion and water depth are important structuring agents which influence the species composition of mixed meadows. Furthermore, burrowing alpheid and callianassid shrimp fulfill important roles in the meadows by enhancing nutrient recycling and controlling the lower boundary of the meadows. It is concluded that both abiotic (water motion and depth) and biotic (e.g. shrimp) factors affect the capacity of top-reef seagrass meadows to process and sequester carbon. The potential impact of sea level rise and ocean acidification on these meadows is also discussed.